Importancia de la seguridad y bienestar escolar - Remache Guanoluisa, Jorge Eduardo (2017)
It is necessary to approach the issue of safety and school well-being in the educational community, thus being integral protection and self-care, whose objective is to investigate how security and well-being affects the teaching- learning process to safeguard the physical, emotional and social security of students in the teaching-learning process, school safety and well-being guarantees the protection of the entire educational community in the context of which school activities are carried out. This contributes to face risk situations in student welfare, so that orientations in self-care are effective, it is essential to have the active and responsible collaboration of management staff, teachers and students of the educational community. It is fundamental to integrate and strengthen in the members of the institution the participation of the plan of safety and school welfare, with which we can minimize the risks in the educational institution, thus preventing innumerable factors of danger since it has been verified that there are diverse measures of insecurity that they exceed the factors of protection, so it is necessary to deal with the educational personnel in order to protect the physical integrity and avoid various accidents of those who are part of the educational community. Therefore, quantitative and qualitative results were established denoting that the training of teachers plays a very important role in the education and interrelation in the process of prevention and school safety, thus facilitating the importance of defending the physical integrity of each of the members of the institution, for this must have a list of basic rules on comprehensive and personal protection in the teaching-learning process.